A Systematic Review and Meta-Analysis of Prognostic Nomograms After UTUC Surgery - Pallauf, Maximilian; König, Frederik; D’Andrea, David; Laukhtina, Ekaterina; Mostafaei, Hadi; Motlagh, Reza Sari; Quhal, Fahad; Aydh, Abdulmajeed; Yanagisawa, Takafumi; Kawada, Tatsushi; Rajwa, Pawel; Lusuardi, Lukas; et al. (Frontiers in Oncology, 2022)
Background: Current guidelines recommend assessing the prognosis in high-risk upper tract urothelial carcinoma patients (UTUC). However, no specific method is endorsed. Among the various prognostic models, nomograms represent an easy and accurate tool to predict the individual probability for a specific event. Therefore, identifying the best-suited nomogram for each setting seems of great interest to the patient and provider. Objectives: To identify, summarize and compare postoperative UTUC nomograms predicting oncologic outcomes. To estimate the overall performance of the nomograms and identify the most reliable predictors. Design: A systematic review was conducted following the recommendations of Cochrane’s Prognosis Methods Group. Medline and EMBASE databases were searched for studies published before December 2021. Nomograms were grouped according to outcome measurements, the purpose of use, and inclusion and exclusion criteria. Random-effects meta-analyses were performed to estimate nomogram group performance and predictor reliability. Results: The systematic review identified 26 nomograms. Only four were externally validated. Study heterogeneity was significant, and the overall Risk of Bias (RoB) was high. Nomogram groups predicting overall survival (OS), recurrence-free survival (RFS), and intravesical recurrence (IVR) had moderate discrimination accuracy (c-Index summary estimate with 95% confidence interval [95% CI] and prediction interval [PI] > 0.6). Nomogram groups predicting cancer-specific survival (CSS) had good discrimination accuracy (c-Index summary estimate with 95% CI and PI > 0.7). Advanced pathological tumor stage (≥ pT3) was the most reliable predictor of OS. Pathological tumor stage (≥ pT2), age, and lymphovascular invasion (LVI) were the most reliable predictors of CSS. LVI was the most reliable predictor of RFS. Conclusions: Despite a moderate to good discrimination accuracy, postoperative prognostic UTUC nomograms have low generalizability for daily practice. For nomograms to become relevant for treatment decisions, future research must invest in their external validation and assessment of clinical utility.